KOMPARASI ISTIHSAN ANTAR MAZHAB FIKIH DAN PENERAPANNYA DALAM PENETAPAN HUKUM ISLAM - Ilhami, Hanif A'la; Ismail; Asasriwarni (Program Studi Perbandingan Mazhab, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2024)
The existence of differences regarding the validity of istihsan cannot be denied due to differences in understanding its essence. Even among scholars who accept istihsan, both within the Hanafi and Maliki schools, there exist diverse definitions of istihsan. This study attempts to comprehensively explain istihsan through a comparative lens across various schools of thought and how it's applied in establishing Islamic law. The research findings indicate that despite differing opinions among scholars concerning the validity of istihsan, substantively they all utilize it in deducing legal rulings. Hanafi, Maliki, and some Hanbali scholars support and employ istihsan in their ijtihad (independent legal reasoning); meanwhile, Imam Shafi'i and his followers reject istihsan as an evidentiary basis in Sharia law, yet they occasionally use similar methods, though not explicitly referred to as istihsan. The differences in the usage of terms are quite common. Just as in the Hanafi school of usul al-fiqh (principles of Islamic jurisprudence), specific terms are used, such as differentiating between